The mediating role of illness perceptions in psychological outcomes in overactive bladder. Issue 3 (28th July 2014) - Pretorius, Sara; Kinsey, Debbie; Alexander, Tim; Glover, Lesley; Kraus, Sigurd; Duggan, Paul
ABSTRACT Overactive bladder (OAB) is condition, characterized by urinary urgency, frequency and incontinence, which has the potential to disrupt everyday life considerably. Although there is evidence that antimuscarinic treatment is effective at treating physical symptoms, there is currently no systematic exploration of psychological factors associated with OAB after treatment. This study aimed to examine the quality of life, relationships, sexual functioning, psychological wellbeing and illness perceptions of individuals with OAB after they have received treatment. And to determine whether an individual's psychological wellbeing is directly related to the severity of their symptoms, or whether their illness perceptions mediate this relationship. This study used a cross‐sectional, questionnaire‐based quantitative design with a secondary care outpatient sample who were diagnosed with OAB and had been either previously or currently prescribed drug treatment. Patients reported moderately severe OAB symptoms, with approximately a third reporting moderate/severe anxiety and 12% reporting severe depression. There was no direct relationship between symptom severity and psychological wellbeing (β = −0·03, t(31) = −0·96, p = 0·34; β = −0·02, t(31) = −0·41, p = 0·68) – this relationship was mediated by the patient's sense of personal control over their OAB (β = 0·03 (SE = 0·02), 95% CI [0·004, 0·09]; β = 0·02 (SE = 0·02), 95% CI [0·0008, 0·08]). Including interventions to improve personal control alongside drug treatment may improve treatment adherence and outcomes.